LAND REGISTRATION IN URBAN AREAS (URBAN LAND REGISTRY): SPECIAL CHALLENGES OF LAND REGISTRATION IN SURABAYA CITY - Abraham Ferry Rosando; Farida Rosadi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Land registration is a strategic step in ensuring legal certainty over property rights in the Republic of Indonesia. However, in large, densely populated cities like Surabaya, this process faces complex challenges. This article examines specific issues in urban land registration, including abandoned land and squatter settlements. The research uses empirical juridical methods to examine the gap between regulations and implementation on the ground. The study reveals that low public participation, overlapping ownership, and weak law enforcement are key obstacles, alongside socio-economic issues such as squatter urbanization. This article recommends a participatory approach, reformulation of local regulations, and integration of land and housing policies as solutions.